Truth in Criminal and Civil Proceedings: Ensuring Sustainable Development of Society and Social Peace - Kudeikina, Inga; Kaija, Sandra (European Journal of Sustainable Development, 2023)
The right to a fair trial is a key element of the rule of law. It should be noted that the right to a fair trial has a complex structure, because securing this right is both a goal, or a state’s positive commitment to ensuring citizens’ rights, and a means of achieving this goal. The obligation to tell the truth as a principle of procedure constitutes the core of a fair trial. The concept of ‘fair trial’ would be a mere fiction if the state would not demand that parties to the case tell the truth in proceedings. There is no doubt that a dispute can be solved in reliance on true facts, true statements. This is a pre-requisite for the legal resolution of disputes, which means confidence in the judiciary as an element of state’s sustainability in the long run. The objective of the research is to examine the scope of the obligation to tell the truth in procedural relations in conjunction with the need for the fair settlement of legal relationships in the context of the sustainability of society in order to formulate suggestions for improving the legislation, thereby minimising opportunities to avoid the truth for the parties to proceedings.The research has employed descriptive and analytical, deductive and inductive methods. These methods have been used to analyse laws and the opinions of legal scholars and formulate conclusions and suggestions. Keywords: civil proceedings, criminal proceedings, obligation to tell the truth